2013
DOI: 10.1308/003588413x13629960048406
|View full text |Cite
|
Sign up to set email alerts
|

The faciocervicopectoral flap for non-oncological cases of cheek reconstruction

Abstract: INTRODUCTION Major facial defect has been a challenging case for plastic surgeons in terms of wound healing and covering technique for a long time. METHODS Eight faciocervicopectoral (FCP) flaps were performed for reconstruction of major cheek defects due to handmade explosive and gun injuries. They were evaluated perioperatively and postoperatively with regard to operative time and operative blood loss as well as the function and cosmetic appearance. RESULTS The technique showed marvellous cosmetic results b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…The same results were shown by Hagerty et al, [16] for partial nasal reconstruction. Bakamjian et al, revealed the high suitability of deltopectoral flap for head and neck defects covering due to the similarity of color and texture of skin with hidden donor site [8,17]. We agreed with the results of Bakamjian except in some males with hairy chests.…”
Section: Aesthetic Considerationssupporting
confidence: 90%
“…The same results were shown by Hagerty et al, [16] for partial nasal reconstruction. Bakamjian et al, revealed the high suitability of deltopectoral flap for head and neck defects covering due to the similarity of color and texture of skin with hidden donor site [8,17]. We agreed with the results of Bakamjian except in some males with hairy chests.…”
Section: Aesthetic Considerationssupporting
confidence: 90%